Commons Für eine neue Politik jenseits von Markt und Staat - Helfrich, Silke; Heinrich-Böll-Stiftung, undefined (Sozialtheorie, 2014)
Commons - the world belongs to us all! The never-ending global financial crisis shows: Market and state have failed. It is therefore not surprising that Commons, the idea of communal organization and use of common goods and resources, find strong support - not only since the Nobel Prize in Economics was awarded to Elinor Ostrom. Commons are more important than ever. They are not based on the idea of scarcity, but draw from abundance. This volume with contributions by 90 international authors from science, politics, and society introduces a modern concept of Commons that radically questions classic assumptions in theories of economy and property, and outlines a different culture of coexistence.